Avaliação da Atividade Protetora Gástrica do Extrato Hidroalcoólico da Semente de Girassol - Costa, Juslene Aparecida Oliveira da (2009)
Helianthus annus is a plant known as "sunflower". The use of plants as medicine for human use dates back to the old age. The hydroalcoholic extract of sunflower seed (HESS) has been indiscriminately used for gastric lesions, without scientific support to validate their action. This study assessed quantitatively and qualitatively the probable gastric protection of HESS in stress, and in the use of ethanol and indomethacin; checked the acidity (pH) through the gastric pylorus ligation (gastric residue, either pure or added with water); and compared differences in pH values in both techniques. A total of 120 rats (5 in each group) of the species Rattus norvegicus albinus, weighing 150-230g,were divided into 24 groups, which received the following treatments: HESS: 250mg/kg, 500mg/kg, 1000mg/kg and 2000mg / kg; ethanol; cimetidine; indomethacin; water; cimetidine and ethanol; cimetidine and endomethacin; pylorus ligation and water; pylorus ligation and cimeditine; HESS and ethanol; HESS and indomethacin; pylorus ligation and HESS. The results were submitted to analysis of variance (ANOVA) followed by Tukey test for evaluation of gastric lesions, and Kruskal-Wallis test followed by Dunn, to evaluate the gastric pH, with a statistically significance at p <0.05. This work was approved by the Ethics Committee of the Universidade José do Rosário Vellano, with protocol no. 04 A / 2009. The results showed that HESS 250 mg/kg and 1000mg/kg suggests probable gastric protection in stress. In the ethanol-induced gastric ulcer model, the doses of 250 and 1000 mg / kg showed probable gastric protection; the HESS 250 mg / kg + indomethacin, the dose of 250 mg / kg suggests gastric protection. Regarding the pH, the gastric residue, when pure, is more acidic than water, thus indicating that the model of addition of 3 ml of water is increasing the pH, thus proving that the pure pH model is more appropriate and more practical. Therefore, the data obtained in this study show that HESS probably provides gastric protection at certain doses. So, the results show that the sunflower,should be further studied for the development of phytomedicines or new chemicals with antiulcerogenic activity.